Pharmacological management of cystic fibrosis related diabetes. Issue 2 (1st February 2018) - Moheet, Amir; Moran, Antoinette
ABSTRACT: Introduction : There are limited data from randomized clinical trials to guide optimal options for pharmacological treatment of cystic fibrosis related diabetes (CFRD). Current guidelines recommend insulin as the only treatment option for CFRD. Areas covered : Current guidelines for screening, diagnosis and pharmacological agents for treatment of impaired glucose tolerance and CFRD in patients with cystic fibrosis are reviewed. Insights from clinical studies examining the role of insulin therapy in CFRD are presented. Expert commentary : CFRD is the most common extra pulmonary complication of cystic fibrosis, and is primarily related to insulin insufficiency. Insulin is the treatment of choice for CFRD. Insulin treatment is associated with improvement in glycemic control, nutritional status and lung function. Current data does not support use of oral hypoglycemic agents for treatment of CFRD.